IMPLEMENTASI AKAD MUSYARAKAH MUNTAHIYAH BI AL-TAMLIK DALAM PERSPEKTIF MASLAHAH - A. Zaky Fuad; Iffatin Nur (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2021)
The purpose of writing this article is to find out what the musyarakah muntahiyah bi al-tamlik contract is and how to implement it. Broadly speaking, this contract consists of two keywords, namely musyarakah and tamlik (ownership), which means that this contract is a contract that is carried out is a collaboration between two or more people who promise that at the end of the period it will end with ownership of capital or assets by one. one party in full. The implementation of this contract is carried out by making a syirkah contract first then the second contract can use a sale and purchase contract, a grant or other contract that is justified according to sharia, this is done to avoid the occurrence of multiple contracts in one transaction which usually will lead to the occurrence of gharar. This research is a normative study with a conceptual approach, namely the discussion of the musyarakah muntahiyah bi al-tamlik contract. The extraction of legal materials is carried out through literature studies related to the study of maqashid al-sharia and maslahah both classical and contemporary literature. In determining Islamic law, it often uses maqashid al-sharia which consists of five components, namely maintaining religion (hifdz al-din), guarding the soul (hifdz al-nafs), maintaining reason (hifdz al-'aql), maintaining descent (hifdz al -nasl) and safeguarding property (hifdz al-maal), so that in this transaction no party feels burdened because in the practice of the Islamic home ownership cooperation, they can occupy the house first and make repayments at the end of the contract period so that later the house will become the property. syarik as a whole.